Teach yourself visually Chromebook - Hart-Davis, Guy (Teach yourself visually., 2021)
Provides two-page lessons with step-by-step screen shots that show readers how to tackle useful Chromebook tasks, including configuring Chrome OS, connecting external devices, running and managing apps and extensions, surfing the web, and troubleshooting network problems.